Job mismatches and labour market outcomes - Kostas Mavromaras; Séamus McGuinness; Nigel O'Leary; Peter Sloane; Yin King Fok (The Economic and Social Research Institute (ESRI), 2009)
Interpretation of the phenomenon of graduate overeducation remains problematical. In an attempt to resolve at least some of the issues this paper makes use of the panel element of the HILDA survey, distinguishing between four possible combinations of education/skills mismatch. For men we find a significant pay penalty only for those who are both overskilled and overeducated, while for women there is a smaller but significant pay penalty in all cases of mismatch. Overeducation does not have any negative effect on the job satisfaction of either men or women, while overskilling either on its own or jointly with overeducation does so. Finally, overeducation has no significant effect on the job mobility of either men or women, though there is a significant positive effect on both voluntary and involuntary job loss in men who are both overskilled and overeducated, with the results again differing for women. At least for a substantial number of workers it appears, therefore, that overeducation represents a matter of choice (or is possibly a consequence of low ability for that level of education), while overskilling imposes real costs on the individuals concerned.
Keywords: J24; J31; 330; overeducation; overskilling; wages; job mobility; job satisfaction; gender; Unterbeschäftigung; Bildungsabschluss; Akademiker; Beschäftigung; Zufriedenheit; EU-Staaten